2019
DOI: 10.1111/jopy.12481
|View full text |Cite
|
Sign up to set email alerts
|

Transcendent motivations and virtue development in adolescent marathon runners

Abstract: Objective To understand how health, prosocial, and spiritual motivations correspond to changes in the virtues of self‐control, patience, and interpersonal generosity among adolescents and emerging adults. Method Participants included adolescent and emerging adult athletes (N = 396; 12–22 years, M = 18.42, SD = 2.03) on marathon training teams fundraising for a faith‐based charity. Participants completed self‐report questionnaires four times over six months. Participants were 63% female and identified as 61% Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 56 publications
(77 reference statements)
1
6
0
2
Order By: Relevance
“…Findings from this dataset reporting bivariate latent growth curves models relating motivations (spiritual, prosocial, health) to the development of three virtues (self-control, patience, and interpersonal generosity) have been previously published [20]. In addition, a manuscript analyzing these data is under review proposing a multi-factor structure for self-control that predicts race completion and race times [63].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from this dataset reporting bivariate latent growth curves models relating motivations (spiritual, prosocial, health) to the development of three virtues (self-control, patience, and interpersonal generosity) have been previously published [20]. In addition, a manuscript analyzing these data is under review proposing a multi-factor structure for self-control that predicts race completion and race times [63].…”
Section: Methodsmentioning
confidence: 99%
“…Not only is generosity an indicator of positive adjustment during adolescence and emerging adulthood, but it also launches a trajectory of generativity that may continue across the life course [19]. Previous research has demonstrated that changes in generosity are predicted by initial levels of prosocial and spiritual (but not health) motivations among adolescents training for charitable marathons, and changes in generosity are also predicted by changes in prosocial motivations [20].…”
Section: Generositymentioning
confidence: 99%
See 1 more Smart Citation
“…En ese sentido, las motivaciones han sido agrupadas en dos componentes: en primer lugar se encuentran las motivaciones internas que parten de necesidades, las cogniciones y emociones de las personas; en cambio las motivaciones externas pretenden determinar el comportamiento de los estímulos o el conjunto de hechos externos que permiten cambiar la conducta a partir de consecuencias sociales, ambientales y culturales (López-Arellano et al, 2017). Sin embargo, existe otra componente que ayuda a explicar mejor la motivación, por lo que se añade la motivación trascendente, la cual hace referencia a la consecuencia de una determinada acción que un individuo realiza y tiene un efecto en los demás indirectamente (Cedeno, 2004;Sánchez, 2019;Sanizaca, 2018;Schnitker, Gilbertson, Houltberg, Hardy, & Fernandez, 2020).…”
Section: Introductionunclassified
“…La motivación trascendente promueve el bienestar del personal que se refleja en los desempeños efectivos. Además, está más relacionado al aspecto cognitivo, bajo una cosmovisión de creencias, valores y principios del individuo, lo que lleva a un bienestar total y al deseo de aprender (Guerrero, La Rosa, & Díaz, 2015;Schnitker et al, 2020).…”
Section: Introductionunclassified